Economic and carbon emission impacts of electricity market transition in China: A case study of Guangdong Province. (15th March 2019) - Lin, Jiang; Kahrl, Fredrich; Yuan, Jiahai; Chen, Qixin; Liu, Xu
Highlights: Significant potential cost savings to electricity consumers from market reforms. Average market revenues fall to the level of a medium-efficient coal unit. Mechanisms to allow generators to recover their fixed costs are likely necessary. Emissions may increase in the short run, but can be offset by higher hydro imports. CO2 pricing does not reduce emissions in the short run and may lead to significant wealth transfers. Abstract: China's electricity system is the world's largest, in terms of installed generating capacity, and is also the world's largest single source of greenhouse gas emissions. In 2015, China embarked on reforms in its electricity sector that aim to introduce market mechanisms in wholesale pricing. This study provides a quantitative assessment of the economic and carbon dioxide (CO2 ) emission impacts of transitioning to electricity markets in China, focusing on Guangdong Province. We find that market reforms deliver significant annual cost savings (21 to 63 billion yuan, 9%–27% reduction in total costs in a base case) to consumers in Guangdong, with smaller production cost savings (12 billion yuan, 13% reduction in production costs in a base case). Savings for consumers are accompanied by a large reduction in net revenues for coal and natural gas generators, raising concerns about generator solvency, longer-term resource adequacy, and the need for transition mechanisms. Market reforms increase CO2 emissions in Guangdong, as a result of gas-to-coal switching, though higher hydropower imports from neighboring provinces could offset these emissions. CO2 pricing has a limited impact on CO2 emissions in the short run and has the potential to lead to significant wealth transfers. The most important benefit of market reforms will be in providing an economic framework for longer-term operations and investment.